2014
DOI: 10.4103/1319-2442.135229
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of sepsis-associated acute kidney injury in an intensive care unit: An experience from a tertiary care center of central Nepal

Abstract: Acute kidney injury (AKI) is a common and major complication of sepsis. Sepsis-induced AKI is associated with higher morbidity and mortality. A prospective study was designed to include all the patients with a provisional diagnosis of sepsis with AKI admitted in our intensive care unit from August 2009 to September 2010. Detailed demographic data including various clinical parameters, co-morbidities, investigations, complications and outcome were entered in a designated proforman and were analyzed. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
2
9
0
2
Order By: Relevance
“…Pneumonia was the leading cause in the study of Madav et al. in Nepal followed by gastroenteritis and urinary tract infection [ 35 ]. In contrast, gastroenteritis was the first etiology in the studies of Praskash et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia was the leading cause in the study of Madav et al. in Nepal followed by gastroenteritis and urinary tract infection [ 35 ]. In contrast, gastroenteritis was the first etiology in the studies of Praskash et al.…”
Section: Discussionmentioning
confidence: 99%
“…15 A study carried on outcome of sepsis associated acute kidney failure injury in intensive care unit recognized pneumonia the major medical illness. 16 The use of vasopressor such as norepinephrine, epinephrine and dopamine were found significantly more in deceased group than in survivors. Empiric antibiotic administration is initiated in emergency department as early as possible so as to prevent further worsening of problem.…”
Section: Discussionmentioning
confidence: 94%
“…[32][33][34] Renal function Acute kidney injury (AKI) is due to inflammation reaction, endothelial injury and microcirculation disturbance, which were induced by sepsis. Studies [35,36] revealed that 50% of patients with AKI were induced by sepsis in the ICU, suggesting that sepsis is the main cause of AKI. AKI is regarded as an independent risk factor of death in septic patients.…”
Section: Clinicians Should Perform Arterial Blood Gas Analysismentioning
confidence: 99%